A new flat mite genus and five new species (Tetranychoidea: Tenuipalpidae) from native Australian sedges (Cyperaceae) - Beard, Jennifer J.; Seeman, Owen D. (Zootaxa, 2025)
Five new species of Tenuipalpidae are described with a new genus Scleriacarus Beard & Seeman from native Australian sedge species (Cyperaceae)—Scleriacarus gilberti gen. nov. sp. nov. and Acaricis scleriae sp. nov. from Scleria sphacelata, Aegyptobia gahnia sp. nov. from Gahnia radula, Prolixus asperus sp. nov. from Gahnia aspera, and Prolixus insignis sp. nov. from Gahnia insignis. Aegyptobia gahnia sp. nov. represents both the first record of the predominantly grass-associated mcswaini species group in Australia and the first record of this genus from a sedge.